Pengaruh Pengelolaan Pembelajaran dan Motivasi Belajar Terhadap Hasil Belajar Peserta Didik - Ratna Aliyas; Muh Ilyas Ismail; Andi Maulana (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2019)
This research aims to analyze and examine the influence of learning management and learning motivation to learning outcomes of students in Madrasah Tsanawiyah Pondok Pesantren Nurul Falah Borongganjeng, Bulukumba Regency. This research is classified as quantitative research with the ex post facto method. Respondents in this study as many as 38 learners taken randomly from 127 students. The data collection techniques used are polls and documentation, whereas the analytical techniques used to examine hypotheses are inferential statistics through regression analysis. The results of this study show that partially, the management of learning has a positive and significant impact on student’s learning outcomes of 10.8% and 89.2% is determined by other factors, as well as the motivation to learn positive influences and of student learning outcomes of 14.2% and 85.8% is determined by other factors. However, the learning management and learning motivation jointly positively affects the student's learning outcomes of 14.9%, but not significant.